Because of you I did not give up - How peers affect perseverance - Leonie Gerhards; Christina Gravert (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Various empirical paper have shown that peers affect productivity and behavior in the workplace. However, the mechanisms through which peers influence each other are still largely unknown. In this laboratory experiment we study a situation in which individuals might look at their peers' behavior to motivate themselves to endure in a task that requires perseverance. We test the impact of unidirectional peer effects under individual monetary incentives, controlling for ability and tactics. We find that peers significantly increase their observers' perseverance, while knowing about being observed does not significantly affect behavior. In a second experiment we investigate the motives to self-select into the role of an observing or an observant subject and what kind of peers individuals deliberately choose. Our findings from this treatment provide first insights on the perception of peer situations by individuals and new empirical evidence on how peer groups emerge.
Keywords: C91; M50; J24; 330